ANALISIS KORELASI ANTARA LAJU INFLASI DAN TINGKAT PENGANGGURAN AKIBAT PHK MASSAL - Nursalamah Nursalamah; Kartika Nurrosidah, Mayla Tania, Julia Rahma Sahara, Suci Hayati (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study is to examine the relationship between unemployment rates caused by mass layoffs and inflation rates. The economic crisis has resulted in layoffs and a widening gap between the supply of low-wage job opportunities and the growth of the new workforce. As a result, Indonesia's unemployment rate continues to increase every year. Through a literature review, this study uses a qualitative methodology. Primary and secondary literature sources are collected to conduct the research process. Descriptive qualitative research is a type of this research. Research methods based on descriptive data processing are known as descriptive qualitative research methods. According to the findings of this study, the loss of jobs and income caused by mass layoffs has increased unemployment and poverty rates as affected individuals and families find it difficult to meet their basic needs. An inverse relationship between inflation and unemployment rates is empirically observed without a strong theory; that is, if inflation increases, unemployment decreases, and if inflation decreases, unemployment increases. Thus, the inflation rate and unemployment rates due to mass layoffs have a correlation or relationship that is interrelated and inverse.